Dupilumab in pediatric atopic dermatitis: real-world evidence from two national centers - Rosa,Gilberto P. da (2024)
Abstract Objective: The use of dupilumab in children with atopic dermatitis (AD) demonstrated clinical efficacy in clinical trials. Nevertheless, real-world evidence is still limited. We aim to provide data on this matter regarding a Portuguese pediatric population. Methods: Retrospective analysis of patients with AD below the age of 18 treated with dupilumab in two Portuguese hospitals. Data regarding previous therapies, activity scores, and adverse reactions were collected. Results: Thirty patients were included in the analysis (19 male patients, 63%), with a median age of 14 years (2-17 years). The median follow-up after starting treatment was 80 weeks. The median baseline Eczema Area and Severity Index (EASI) score was 32.3. Sixty percent of patients achieved EASI-90 and 77% EASI-75 at week 16 (n = 30); 79% EASI-90 and 92% EASI-75 at week 52 (n = 24); 64% EASI-90 and 82% EASI-75 at week 104 (n = 11); and 75% EASI-90 and 100% EASI-75 at week 132 (n = 4). Regarding adverse reactions, four patients (12%) presented facial erythema and two patients had eosinophilia above 2000/μL and conjunctivitis. In five patients (17%), there was a need for a dose increase, with treatment failure occurring in two patients (7%). Conclusion: Our data corroborated the evidence from clinical trials, highlighting the maintained efficacy and adequate safety profile of dupilumab in this age group.